CHINA’S GAS POLICY IN CENTRAL ASIA - MATVEEV, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2008)
The development of China’s gas industry cannot be reviewed outside the context of the development problems that have arisen throughout its entire energy sphere. The growth of the Chinese economy in the midterm is largely related to the increase in the share of consumption of efficient energy resources—natural gas, oil, hydro-, and nuclear power, although at present their share in the production structure of energy resources is relatively small. But drawing effective energy resources into circulation is fraught with a fair number of problems. At the present time, the high rates of growth in the Chinese economy are not sustained by corresponding development in the fuel and energy complex. The PRC is increasingly becoming a net importer of energy resources. Over time, the shortage of energy resources will only rise, and meeting the needs of the national economy for them in full measure will become one of the active factors in the state’s foreign policy strategy. A key facet of China’s energy diplomacy is stable and guaranteed provision of the country’s needs for highly efficient energy resources, meaning oil and natural gas. Due to the PRC’s extensive involvement in the globalization processes, significant attention should be given to such external factors of world energy market movement as a change in the geopolitical situation and the related in crease in political risks and instability in hydrocarbon production, increase in world prices for oil and gas, greater state participation in world energy resource trade, and so on.